Response of rat bone marrow cells to commercially pure titanium submitted to different surface treatments - Xavier, S. P.; Carvalho, PSP; Beloti, M. M.; Rosa, A. L. (Elsevier B.V., 2003)
Objectives. Alterations in the commercially pure titanium (cpTi) surface may be undertaken to improve its biological properties. The aim of this study is to investigate the biocompatibility of cpTi submitted to different surface treatments.Methods. The cpTi surfaces were prepared so that machined and blasted surfaces, either acid etched or not, were compared using rat bone marrow cells cultured to differentiated into osteoblast. For attachment evaluation, cells were cultured for 4 and 24 h. Cell morphology was evaluated after 3 days. After 7, 14, and 21 days cell proliferation was evaluated. Total protein content and alkaline phosphatase (ALP) activity were evaluated after 14 and 21 days. For bone-like nodule formation, cells were cultured for 21 days. Data were compared by analysis of variance.Results. Cell attachment, cell morphology, cell proliferation, and ALP activity were not affected by surface treatments. Total. protein content was reduced by blasted and acid etched surface. Bone-Like nodule formation was significantly reduced by blasted, acid etched, and a combination of both blasted and acid etched surfaces.Conclusions. Based on these results, it can be suggested that cpTi surfaces that were submitted only to machining treatment favor the final event of osteoblastic differentiation of the rat bone marrow cells, evidenced by increased bone-Like nodule formation. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: biocompatibility; rat bone marrow cell; surface treatment; titanium